P672 Drug therapy and monitoring for inflammatory bowel diseases: preliminary data from a multi-centre investigation in Asia. (25th January 2019) - Cai, C; Shen, J; Tong, J; Lu, J; Zheng, Q; Wu, K; Qian, J; Ran, Z
Abstract: Background: There is a growing population of patients with inflammatory bowel diseases (IBD) in Asia in recent years. The present investigation intended to obtain a better understanding of the current situation on drug therapy and monitoring for IBD from physicians' viewpoints in Asian areas. Methods: A questionnaire investigation about drug therapy and monitoring for IBD was conducted in Asia before the sixth Annual Meeting of Asian Organization for Crohn's and Colitis (AOCC). Questionnaires were sent to AOCC members to fill out via email between March and May 2018. Results: One hundred and sixty-nine physicians of 132 medical centres from Mainland China, Hong Kong, Taiwan, Japan, South Korea, India, Malaysia, Singapore and Thailand responded to the survey, in which 74 centres from all parts of Mainland China except Tibet participated. The average number of consultant gastroenterologists with specialist IBD experience of the investigated centres was 4.8 in Taiwan, which was the most among the surveyed regions. Mainland China had the largest average number of 2.5 of IBD specialist nurses in their centres. 5-aminosalicylic acid (5-ASA)/sulfasalazine (SASP) (99.41%) was the most preferred first-line choice for mild–moderate ulcerative colitis (UC), then followed by steroids (34.9%) and azathioprine (8.9%). Steroids (84.7%) were widely applied for severe UC, followed by infliximab (29.8%), 5-ASA/SASP (20.3%), azathioprine (14.9%) and ciclosporin A (11.9%). The first-line medication for Crohn's disease (CD) markedly varied among the responders as steroids (69.1%) were the most preferred in Mainland China, Japan and South Korea, followed by infliximab (52.3%), azathioprine (46.5%), 5-ASA/SASP (42.5%) and adalimumab (11.4%). Step-up strategy for mild–moderate UC was adopted by a large majority of physicians (96.4%) while it was only favoured by 36.1% physicians for severe UC. For CD, top-down treatment was adopted by 51.5% physicians while 39.1% chose step-up. For therapeutic drug monitoring, only 19.4%, 37.1%, 41.2%, 25.9% and 17.7% of the centres were able to test blood concentration of 6-mercaptopurine, FK506, ciclosporin A, infliximab and antibody to infliximab, respectively. The frequency for monitoring adverse events of IBD medication varied from 1 week to 6 months according to responders' answers. Conclusions: The quantity of medical personnel with specialist IBD experience, the availability of IBD drugs and the preferences for drug choice vary from region to region in Asia. Therapeutic drug monitoring is insufficient in most investigated areas, which suggests little optimism in quality of drug therapy. Asian version of recommended indicators for drug therapy and monitoring is encouraged to be established for further improvement of IBD management.